Geotechnical characterization of gold mine tailings and wastes from aggregate quarry in the Philippines - Adajar, Mary Ann Q. (2012)
Despite the economic benefits, mining operatons in the Philippines often face strong opposition from affected communities because of its adverse environmental and social effects. Foremost of these is the generation of huge amounts of waste materials called mine tailings. The disposal of the enormous amount of tailings regularly produced from mining operations is the most common environmental issue associated with mining activities. Tailing dam as storage facility plays an important role in the waste management of mining industries but failure of this structure, while the mine tailings are still in slurry form, can result in a debris flow that poses a serious threat to life, property and the environment . Reducing the volume of tailings stored in impoundment facilities can reduce the risk to the exposed populations and the environment and can reduce storage costs. One method for achieving this goal is to utilize tailings that do not contain deleterious components as backfill or embankment materials in the construction of tailing dams. In this study, mine tailings collected from concrete aggregate quarry and gold mines in the Philippine are geotechnically characterized for the purpose of determining their suitability as fill or embankment construction material. Standard ASTM procedures are performed to obtain the physical characteristics such as grain size distribution, Attenberg Limits, specific gravity, minimum and maximum index densities and compaction behavior. Results of these tests indicate that tailings from aggregate quarry can be classified as poorly graded sand with silt (SP-SM) while gold mine tailings can be classified as silty sand (SM) under the Unified Soil Classification System. COmpacton tests showed that the moisture versus unit weight relationship is characterized by a concave downard curve with the optimum water content ranging between 13% to 17%, with a maximum dry density ranging from 15.6 kN/m3 to 17.7 kN/m3. Microfabric analyses performed using electron microscopy showed a microstructure that is granular with some flaky particles. Failing head permeability tests are performed on reconstituted samples compacted at varying void ratio and fine contents. The hydraulic conductivity, k of tailings falls within the range of 10^-3 to 10^-6 cm/sec. A new relation for predicting hydraulic conductivity of non-plastic fine tailings was formulated. The proposed analytical model is capable to taking into consideration the effect of void ratio and fine contents on the hydraulic conductivity. Comparison of the proposed model with existing analytical models show significantly better agreement of the proposed model with experimental data.
Stress-strain behavior of tailings from one-dimensional consolidation was evaluated and consolidation paramterswere determined. The values of consolidation parameters from oedometer tests indicate that tailings are classified as slightly compressible. Gold mine tailings from Davao were shown to be 40% more compressible than aggregate tailings and tailings from Masbate. The hydrocompression settlement of tailings was also determined and a new procedure for determining the hydrocompresison strain was proposed. The procedure is appropriate for use even with the samples that do not exhibit secondary compression. Tests results revealed that tailings are less susceptible to hydrocompression. Polynomial relationships were developed to determine the hydrocompression settlement as a function of vertical stress. Tailings' shear strength behavior was investigated through direct shear tests. Tailings in dry condition manifested a strong particle interlock as indicated by high critical state friction angle ranging from 36.6 deg. to 38.4 deg. Critical state parameters were determined to predict the combination of shear stress, normal effective stress and specific volume that will cause failure. Saturated tailings when sheared fast resulted to reduction in shear strength. Drained condition of tailings is achieved through the use of strain rate not greater that 0.12mm/min. Friction angles at failure of saturated tailings were lower at an average of 4 deg. as compared to those obtained in dry condition. Modified hyperbolic model was formulated to predict shear stress vs. shear strain and volumetric strain vs. shear strain responses of tailings measured from the direct shear test. In the modified hyperbolic model, the hyperbolic relation between the changes in stress and strains is defined in terms off an initials shear modulus, Gi, and the shear strength at failure, Tf. The model introduced new hyperbolic parameters, the volumetric strain-shear strain responses measured during tests of specimens that exhibited a ductile failure and compressive volumetric strain. However, the model does not give a good prediction of stress-strain response for specimes that showed brittle failure with dilative volumetric strain. High values of friction angles, good compaction behavior, low compressibility and less susceptibility to hydrocompression manifested by tailings in this study are indication that they are suitable as materials for geotechnical application.
"October 2012."
Thesis (Ph.D. Civil Engineering major in Geotechnical Engineering)--University of the Philippines, Diliman.
Keywords: Gold mines and mining -- Philippines; Engineering geology